Statement of Problem Template - Dusim, Haidy Henry (2020)
Writing a clear problem statement in research helps the reader to understand the purpose of the study more clearly. However, writing a clear problem statement still becomes an issue. As a result, the reader unable to understand what is the purpose of the research. Hence, this innovation aims to develop a statement of problem template on how to write a clear problem statement. Through this template, researchers may able to have better guidelines on developing a clearer problem statement.